Prevalence of dry eye at high altitude: A case controlled comparative study - Gupta, N.; Prasad, I.; Himashree, G.; D'Souza, P. (High Altitude Medicine & Biology, 2008)
High altitude is associated with physiological as well as pathological changes in the eye related to adverse environmental conditions that result in increased tear evaporation and contribute to a higher incidence of dry eye in these regions. We aimed to study the difference in prevalence of dry eye at high altitude and at low altitude. The prevalence of dry eye among the natives and the army soldiers who were recently posted at high altitude was also studied and compared. 200 adults above 20 years of age were enrolled. 100 subjects were recruited at a high altitude region (study group), of which 50 were native Ladakhis and 50 were soldiers recently posted at Leh, Ladakh, India (height; 3300 m above sea level; temperature: 18°C to 24°C). 100 subjects, age and sex matched, were screened at a low altitude region, New Delhi, India (218 m above sea level; temperature: 19°C to 24°C) to serve as the control group. Prevalence of dry eye was assessed through standard questionnaires (McMonnies' Questionnaire (MMI), Ocular Surface Disease Index Questionnaire (OSDI), and Schirmer's basic secretion test. On the basis of the parameters studied (symptoms, MMI, OSDI and Schirmer's test), dry eye was diagnosed in 20% of subjects screened at high altitude and in 9% of subjects in the control group screened at low altitude. In the study group, the prevalence of dry eye was significantly higher amongst the native population (54%) than in the army soldiers who were recently posted at that region (26%). The difference was statistically significant (p < 0.005). In conclusion, dry eye is more common at high altitude, particularly in the native population. Awareness among people residing at high altitude and the treating medical personnel needs to be created for early detection and treatment of dry eye to prevent vision-threatening complications.